Provision of free medicines to patients with epilepsy - A. P. Gertsen; V. V. Rumyantsev; A. A. Iskanderova; A. A. Bakitova (Русский журнал детской неврологии)
Epilepsy is a common disease of the nervous system that requires long-term (often lifelong) use of drugs that allow many people with this diagnosis to lead an active social life with no risk of disability or life-threatening situations. Despite the existing normative acts regulating the provision of free medicines to epilepsy patients, there are still many problems associated with the compliance with the current legislation (Constitution of the Russian Federation) and the availability of free medicines for patients with epilepsy. In this article, we tried to cover the main norms of the current legislation regulating the issues of providing patients with epilepsy with free medicines; this can be helpful for both physicians and patients in overcoming bureaucratic barriers when confronting medical officials in defending the rights of patients.